Adolescent girls and young womens' perspectives of how their lives were impacted by participating in a combination HIV-prevention intervention in South Africa: a qualitative study - Verwoerd, Wilmé (Department of Public Health and Family Medicine, 2021)
Background: HIV incidence among adolescent girls and young women (AGYW) aged 15-24 in sub-Saharan Africa remains exceptionally high. Evidence shows that no single HIV prevention strategy will be effective in controlling the HIV pandemic. Research in recent years demonstrates the need for combination HIV prevention efforts, including biomedical, behavioral, and structural interventions. Given the urgent need to identify strategies that effectively reduce HIV risk among AGYW, it is crucial to understand how best to maximize the impact of combination HIV prevention interventions. This qualitative study explored the perceived impacts of a combination HIV-prevention intervention on the lives of AGYW in South Africa. Methods: The study is based on the findings from a qualitative evaluation of the RISE Club Programme, one component of a combination HIV intervention for AGYW. Using 24 focus group discussions and 63 in-depth interviews with 237 AGYW, we explored participants' experiences and perceptions of participating in a combination HIV prevention intervention and how it was perceived to impact their lives. Results: From the perspectives of AGYW, the intervention was perceived to positively impact their ability to communicate and develop and maintain healthy relationships with family, peers and partners. The findings show that the intervention helped increase their sexual and reproductive health (SRH) knowledge which improved their sexual self efficacy while also encouraging positive behavioural choices such as contraceptive uptake. It was also perceived to improve AGYW lives and personal development, specifically their self confidence and self esteem. However, logistical challenges with the implementation of the intervention and unmet expectations, created frustration and negative perceptions of the intervention in some instances. Conclusions: Overall, the findings demonstrate that intervention recipients perceived mostly positive impacts on their lives as a result of participating in the RISE programme. Understanding the perspectives of AGYW, is helpful in order to assess the benefits and perceived impacts of such an intervention on the lived realities of intended beneficiaries. Taking these perspectives into consideration and understanding some of the unforeseen negative impacts of the intervention can help to inform the design and implementation of future combination HIV prevention interventions for a similar sub-group of the population.